PENGARUH SELF-CONCEPT DAN LITERASI DIGITAL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK - Munif, Fika Aisyah; Yuwono, Muhammad Ridlo; Wijayanti, Septiana (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2024)
Based on the demands of the curriculum, it is expected that students can master various mathematical abilities such as the ability to solve mathematical problems.There are various elements that can influence students' skills in solving mathematical problems. This study aims to find out that there is no effect of positive self-concept on students' ability to solve mathematical problems, there is no positive effect of digital literacy on students' ability to solve mathematical problems, and there is no effect of positive self-concept and digital literacy simultaneously on problem-solving abilities. student mathematics. This research is included in quantitative research. The population is class X students of SMK Negeri 3 Klaten with a total of 432 students. Data collection applies questionnaire techniques, tests and documentation. The collected data were analyzed by simple linear regression analysis and multiple linear regression analysis. The prerequisite tests carried out were the normality test, linearity test and multicollinearity test. The data that has been analyzed shows that there is a positive influence between self-concept on the ability to solve mathematical problems as evidenced by and there is a positive effect between digital literacy on the ability to solve mathematical problems as evidenced by . Furthermore, the results of the study indicate that there is a positive influence between self-concept and digital literacy together on mathematical problem solving abilities as evidenced by .